Putusan Uitvoerbaar bij Voorraad: Rasionalisasi Hakim dan Implikasi Hukumnya - Dwithia H.P., Zora Febriena (Universitas Widya Gama Malang, 2024)
An immediate decision or a decision that can be implemented first (Uitvoerbaar bij Voorraad) is a judge's decision that can be implemented (executed) even though it has not yet obtained permanent legal force. Usually, the implementation of a decision or execution can only be carried out if it has passed the time frame given by the court to file a legal remedy that is against the judge's decision at the first level within 14 days after the decision is read or notified. If within that time frame the losing party does not file any legal remedies, then the decision of the District Court can be implemented or executed. However, in the Civil Procedure Code it is possible for a Judge to pass a UBV decision or a decision that can be implemented first without having to wait for the time span for the losing party to file a legal remedy against the conditions as stated above. Such a decision has the potential for considerable risk considering that there is still the possibility that the judge's decision at the first instance court may be revised or even annulled by a judge at a higher level court. This paper analyzes the rationalization of judges in imposing UBV decisions and the legal consequences of UBV decisions which are canceled by the high court. This research is a normative juridical research with a statutory approach and a concept approach. Based on the results of the analysis, it can be concluded that the rationalization of the judge in imposing the UBV decision is if one of the several conditions that render the UBV decision has been fulfilled, including the claim based on an authentic right, the existence of a judge's decision that has been inkracht, the existence of a provisional lawsuit that has been granted, and the case is related to the bezitsrecht dispute. The legal consequence if the UBV decision is canceled by the high court is that the UBV decision is null and void.